PENGARUH PERBEDAAN PERMANEN, PERBEDAAN TEMPORER DAN LIKUIDITAS TERHADAP PERTUMBUHAN LABA (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016-2020 - Muhammad Ichwan; Krisna Sudjana; Rika Rahmawati (JURNAL ILMIAH EDUNOMIKA, 2023)
The company tries to maximize profits so that they appear to increase in a certain period by manipulating financial statements, through accounts whose provisions can be determined by the company. However, the government has compiled financial reporting standards that companies must comply with so that after the fiscal financial statements there are several accounts that will change and affect the value of net income for a certain period. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange with a research period of 2016-2020 and totaling 15 companies. The sampling technique used was purposive sampling and obtained a sample of 12 companies. The research hypotheses were tested using classical assumption test, descriptive analysis, multiple linear regression analysis, F test and t test. The results of the regression test show that 1.6% of earnings growth factors can be explained by permanent differences, temporary differences and liquidity while the remaining 98.4% is explained by other factors not examined in this study. While the F test shows that simultaneously permanent differences, temporary differences and liquidity simultaneously have no effect on profit growth with the results of the analysis Fcount = (1,190) < Ftable = (2,89). The results of the t-test show that the variables of permanent difference are the results of the analysis of tcount (1.557), temporary difference (1.140), liquidity (-0.246) where ttable (2.035) then partially these variables have no significant effect on profit growth.